Frequency and risk factors of dermatological infections in patients attending dermatology outpatient department of tertiary care hospital - Luqman, Naima; Asgher, Rabia; Amin, Ammara (Journal of Pakistan Association of Dermatologists, 2024)
Objective Dermatological infections are highly prevalent globally thus significantly impacting individual’s quality of life and these infections have many associated risk factors. The objective of this research is to investigate the frequency of dermatological infections and the factors associated with them among individuals seeking care at a Dermatology Outpatient Department in Bahawalpur. Methods A Cross Sectional study was conducted at the Outpatient Department of Dermatology, Bahawal Victoria Hospital Bahawalpur, spanning a period of six months from July 1,2023 to December 31, 2023. All patients seeking treatment for skin concerns during this period were enrolled. Each patient underwent a comprehensive medical history review and thorough skin examination. Results This study was conducted on 1200 patients attending dermatology outpatient department, Bahawal Victoria Hospital, Bahawalpur. This study revealed that 720 (60%) patients were suffering from dermatological infections, 288 (40%) patients had fungal infections, 230 (32%) were suffering from scabies, 116 (16%) had bacterial infections and 36 (5%) were infected with viruses. Conclusion Among all dermatological infections, fungal infections emerged as the most common dermatological infection, followed by scabies, bacterial, viral and parasitic infection. Health education has a great role in controlling preventable risk factors of infections like BMI and hygiene.